Evaluation of the effect of an anti-microbial paint in the UP Pilot Food Plant - Maralit, Jessica F.
The effectiveness of an antimicrobial paint to control contamination in the U.P. Pilot Food Plant was evaluated. The first phase involved the isolation and characterization of the microorganisms in the food plant. Seventeen microbial isolates were obtained which were found to be composed of only 9 types. In the second phase, the effectivity of the sample strips of antimicrobial paint was tested against the microbial isolates from Phase I. Zones of inhibition ranged from .1-1.7 mm. The largest values (1.2 and 1.7 mm) were exhibited by the mold isolates. Some of the isolates did not exhibit zones of inhibition. In the third phase, the paint was applied in the U.P. Pilot Food Plant and its effectiveness over a 6-week period was evaluated using the Swab test. The total plate counts obtained showed an increasing trend indicating that the effectivity of the antimicrobial paint decreased with time.